(untitled) (LACCEI, 2024)
The use of new information and communication technologies (ICTs) has revolutionized not only the ways of living, but also the way of teaching and learning, even more so in the pandemic era, in which confinement led to to the university to a 100% virtual methodology. The objective of this research is to synthesize the evidence on the use of ICTs for remote education in Latin American universities during the Covid-19 pandemic through the systematic review of primary articles indexed in journals such as Scopus, Pro Quest, Redalyc, and others, published between March 2020 and March 2022. The method includes the use of the PRISMA statement, and an explicit flowchart for the selection of articles including inclusion and exclusion criteria, using a keyword search algorithm. Among the results, it was found that 36% of investigations report the use of virtual environments such as institutional platforms or Google Classroom for the development of synchronous and asynchronous classes, 27% developed innovation in educational technology with proposals such as chatbot, teaching telepresence and communication tools. massive evaluation, and 18.5% share experiences in the use of open educational resources, especially gamification tools, and the use of mobile devices, highlighting the use of WhatsApp and Telegram for communication. The country that shows the greatest experiences is Mexico. It is concluded that in the face of the untimely change in modality, and despite situations of uncertainty, technological limitations, coverage and lack of training, Latin American universities evidenced the appropriation of technological tools for their pedagogical practice, during remote education. The findings led us to reflect on the challenges that virtual education represents, in the context of a new normality, in a region where the connectivity gap still represents a limitation